Multiplicação de genótipos de erva-mate pelo processo de estaquia - Santos, Sandra Regina Furini dos (2011)
Commercially, erva-mate (Ilex paraguariensis St. Hil.) is multiplied by seeds, generating high genetic variability and consequently disuniform plants. The alternative to define a genetic pattern is through the vegetative propagation. The objectives of this research were to multiplication of native erva-mate genotypes and to evaluate the rooting potential in cuttings. This paper was carried out in the Horticulture Sector from FAMV/UPF, in Passo Fundo, RS, in a misting system greenhouse. In the cities of Machadinho and Ilópolis, RS, 16 genotypes were selected by their good characteristics. Cuttings were patterned with 12 cm, a pair of leaves was kept by half and the top was eliminated. Cuttings was accomplished in November (spring/summer and herbal stakes) and in March (fall/winter and semi woody stakes), during 95 days in the rooting bed. The cuttings were nurtured by 10 seconds with 6.000 mg L-1 of IBA, compared to the non-nurtured ones. The design was in randomized blocks, in factorial scheme 2 x 16, with four replications and 12 cuttings per plot, being considered each time an experiment. The results showed that the rooting capacity varies among genotypes and that it depends on the cutting time, therefore, in general, when it is accomplished inspring/summer it provides better results than in fall/winter. It was recommended using IBA as being effective in persuading and forming roots. Cutting carried out in the spring/summer and treated with IBA, the genotypes 1, 2, 6, 8, 11, 12 and 15 (Cambona 4) showed a higher rooting (46,7% to 63,6%). For the genotypes 15 (Cambona 4) and 16, with IBA, it is feasible the cutting propagation in the fall/winter, with rooting of 63,7% and 61,1%, respectively. The genotypes capacity to keep the leaves from stakes positively influences in its survival and rooting